THE RELATIONSHIP BETWEEN THE INTENSITY OF PERFORMING SUNNAH WORSHIP AND STUDENTS' ATTITUDE OF SELF-CONTROL (Exploration Study of Madrasah Tsanawiyah Al-Uswah Bergas Semarang Regency) - Setiyowati, Wahyu; Kkhamid, Abdul; Asdiqoh, Siti (LPPM Institut Pendidikan Nusantara Global, 2023)
The problem in this study is the relationship between the intensity of carrying out sunnah worship and the self-control attitude of MTs students. Al-Uswah Bergas, Bergas District, Semarang Regency. In this study it was determined that the population was students of class VII and VIII with a total of 397 students. Henceforth, the samples in this study were 60 students from class VII and VIII. The methods used to collect data are questionnaires, documentation and observation. This study uses a quantitative approach with the Pearson Product Moment correlation analysis method to determine the relationship between the intensity of carrying out sunnah worship and students' self-control by using the SPSS Statistics 21 application. The results showed that: 1) The intensity of the sunnah worship of students from 60 respondents who were in the high category were 28 students or 41%, the medium category were 21 students or 35% and the low category were 11 students or 18%. Thus the intensity of students' sunnah worship is in the high category. 2) The attitude of self-control of students from 60 respondents who were in the high category were 11 students or 18%, the medium category was 23 students or 38% and the low category was 26 students or 43%. Thus the attitude of self-control of students in the low category. 3) There is a significant relationship between the intensity of carrying out sunnah worship and the self-control attitude of MTs students. Al-Uswah Bergas, Bergas District, Semarang Regency.